Clinical and social aspects of dysmenorrhea development - Pakharenko, L. V. (Zaporozhye Medical Journal, 2018)
Dysmenorrhea is one of the most spread diseases in gynecological practice. The pathology rate is about 45–95 % of menstruated women. Aim of the research was to determine clinical and social aspects of women with dysmenorrhea. Materials and methods. The study involved 155 women with diagnosis dysmenorrhea who formed the basic group. 55 persons had primary form of disease (the I group), 100 patients – secondary one (the II group). Control group included 30 women without pathology. Intensity of pain was determined by Visual Analogue Scale, quality of life – 36-Item Short Form Health Survey. For statistical analysis we used program Stаtistica 6.0. Results. We did not find any association between employment, body mass index and development of dysmenorrhea. The number of persons with reduced physical activity was 1.86 times more in the group with dysmenorrhea (61.94 %) than among healthy individuals (33.33 %; χ2 = 7.28, P = 0.007; OR = 3.84, CI = 1.67–8.83, P = 0.002). Gynecological pathology in anamnesis had only 46.67 % of controls and 74.19 % of basic group patients (χ2 = 7.77, P = 0.005; OR = 3.29, CI = 1.47–7.33, P = 0.004). High rate of gynecological diseases among patients with dysmenorrhea was due to great frequency of this pathology in the women of the II group. Almost the same rate of primagravida and multigravida was also among persons in the observed groups. Duration of pain syndrome usually was 1–2 days in the I group women. Persons of the II group indicated prolonged pain syndrome during menses lasting 2–4 days. Besides this, chronic pelvic pain (χ2 = 19.42, P < 0.001 compared to the I group), dyspareunia and dyschezia (χ2 = 5.95, P = 0.03 compared to the I group), pain, which was not connected with menstrual cycle (χ2 = 16.95, P < 0.001 compared to the I group) were typical for patients of the II group. Most women of both groups indicated moderate intensity of pain (67.27 % persons in the I group and 73.00 % in the II). Algomenorrhea, premenstrual syndrome, heavy menstrual bleeding were mostly diagnosed in the persons with secondary dysmenorrhea. All the scores of 36-Item Short Form Health Survey were significantly decreased in basic group patients compared to controls. Index of “Bodily pain” was less by 25.56 % in persons with dysmenorrhea compared with healthy individuals (P < 0.001). Score “Vitality” was the lowest among other indices of psychological component – by 27.27 % (P < 0.001) compared to controls. We determined decrease of “Social Functioning” and “Role-Emotional Functioning” in women with secondary dysmenorrhea more than in patients with primary one (P = 0.049). Conclusions. Among social factors that can lead to dysmenorrhea we found association of reduced physical activity with the development of pathology (OR = 3.84, CI = 1.67–8.83, P = 0.002). Chronic pelvic pain, dyspareunia, pain which is not related to menstrual cycle, are more common symptoms associated with secondary dysmenorrhea compared to primary one (P < 0.05). But there is no difference in intensity of pain between women with primary and secondary forms of pathology. Decreased quality of life is typical for women with dysmenorrhea.